Effect of Nifedipine on Severe Experimental Cataract in Diabetic Rats - Sokichi Kametaka; Takafumi Kasahara; Mayumi Ueo; Mariko Takenaka; Maki Saito; Kenji Sakamoto; Tsutomu Nakahara; Kunio Ishii (Elsevier, 2008)
We examined the effects of Ca2+-channel blockers on sugar cataract formation in streptozotocin (65 mg/kg, i.v.)-induced diabetic rats that were given 5% D-glucose as drinking water. The diabetic rats were treated with an L-type Ca2+-channel blocker, nifedipine or verapamil, for 9 weeks from the 3rd day of streptozotocin injection. Using the full lens images of the horizontal plane captured with the new digital camera system that we developed recently, the cataract formation was quantitatively assessed in parallel with the conventional scaling method. In the animal model of diabetes mellitus, the cataracts at the peripheral region of the lens were detected 2 weeks after induction of hyperglycemia and progressed depending on the length of the diabetic period. The majority of them developed mature cataracts after 9 weeks of hyperglycemia. Nifedipine slowed the progression rate of diabetic cataracts without affecting the period of time required for the onset of this disease, whereas verapamil had no significant inhibitory effect on the diabetic cataract. These findings suggest that nifedipine may be considered as a candidate drug to suppress the progression of diabetic cataracts. Keywords:: cataract, diabetes, lens, L-type Ca2+channel, streptozotocin